2015
DOI: 10.5152/anatoljcardiol.2015.6440
|View full text |Cite
|
Sign up to set email alerts
|

Association between carotid intima-media thickness and presence of coronary artery disease in chronic obstructive pulmonary disease patients

Abstract: Objective:Chronic obstructive pulmonary disease (COPD) is a risk factor for cardiovascular disease (CVD). Carotid intima-media thickness (CIMT) is the sign of subclinical atherosclerosis. Therefore, the aim of this study was to evaluate whether CIMT measurement is related with significant coronary artery disease (CAD) in patients with COPD, similar to those without COPD.Methods:One hundred and eight patients with previously diagnosed COPD and 78 patients without COPD who underwent coronary angiography (CAG) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…Obviously, the longer the duration of COPD, the higher the level of arterial stiffness in COPD patients. This hypothesis has also been clarified by previous studies 2, 3 . In addition, information about drug therapy strategies and lung function in COPD patients is unknown.…”
supporting
confidence: 75%
“…Obviously, the longer the duration of COPD, the higher the level of arterial stiffness in COPD patients. This hypothesis has also been clarified by previous studies 2, 3 . In addition, information about drug therapy strategies and lung function in COPD patients is unknown.…”
supporting
confidence: 75%
“…In 9 studies [19,23,25,26,34,35,37,42,43], we found a significantly higher CIMT in 726 COPD patients than in 2130 controls (MD: 0.10 mm; 95% CI: 0.04, 0.16; p ¼ 0.0007, Fig. 1A), with high detected heterogeneity (I 2 ¼ 94%, p < 0.0001).…”
Section: Cimt and Carotid Plaquesmentioning
confidence: 77%
“…CIMT [19,25,26,34,37,42 and collagen replacement in the extracellular matrix, which result in emphysema in the lungs, and give rise to increased arterial stiffness in the vascular system, have been found in COPD, especially for emphysematous phenotype. Last, COPD might accelerate aging, which facilitates the premature occurrence of systemic complications, such as hypertension, glycemia and cholesterolemia etc [4].…”
Section: N Of Studiesmentioning
confidence: 99%
“…Some studies have also shown that non invasive CIMT measurement might be substitute of invasive angiographic assessment of coronary artery. [14][15][16][17][18][19] Conclusion Although majority studies over a long period of time showed correlation between CIMT and severity of CAD but one study found that severity of CAD did not correlate with CIMT. Risk factors like diabetes, hypertension could be related to increased CIMT.…”
Section: Discussionmentioning
confidence: 99%